Cruise to success : How to steer your way through the murky waters of marketing your library - Phillips, Loreen S.; ScienceDirect eBooks (Oxford [Oxford] : Chandos Publishing, 2009)
Cruise to Success is a hands-on guide and handbook to create a library marketing campaign. Examples and step-by-step instructions assist both the novice and expert in presenting a campaign to attract the campus community to the library's resources.
Introduction -- Why should libraries market themselves? The library as a corporation --Creating a SWOT analysis -- Areas to consider in a marketing campaign -- Merchandising and branding --Marketing strategy -- Poster guidelines -- Other tools of communication: news announcements, public relations, newsletters and annual reports -- References, further reading and resources.
Includes bibliographical references and index.
Elsevier
Keywords: Libraries -- Marketing; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Bibliotecas -- Marketing; Libraries -- Marketing; Marketing; Öffentlichkeitsarbeit; Bibliothek; Electronic books